RHYTHM DISORDERS IN MORPHOLOGICALLY CONFIRMED MYOCARDITIS - D. A. Khashchevskaya; L. B. Mitrofanova; E. S. Ignatieva; D. A. Zverev; D. S. Lebedev; O. M. Moiseeva (Российский кардиологический журнал)
Aim. To reveal the factors determining prognosis in patients with morphologically documented myocarditis presented with rhythm disorders.Material and methods. Totally, 75 patients studied with lymphocyte infiltration myocarditis, 22 patients with dilated cardiomyopathy (DCMP). All patients underwent standard echocardiographic investigation, enhanced magnetic-resonance tomography, endomyocardial biopsy, viral genome molecular test, standard laboratory panel and autoantibodies profile in blood serum. Control group included 30 almost healthy individuals.Results. There were no established differences between the groups with or without rhythm disorders by the activity of inflammatory process and prevalence of viral genome finding in myocarditis patients. The similarity was found for autoantibodies profile in DCMP and myocarditis with rhythm disorders that probably related to fibrous changes in myocardium.Conclusion. The course of arrhythmia development in inflammatory myocardium diseases has complicated multifactorial nature related to a direct harm by infection, to development of autoimmune reactions and structural remodeling of myocardium. Not the arrhythmias influence prognosis, but structural changes in myocardium associated with the decrease of its global contractility.